Analisis Pengaruh Economic Value Added (Eva), Return On Asset (Roa), Return On Equity (Roe) Terhadap Harga Saham Di Perusahaan Manufaktur (Studi Kasus Perusahaan Food And Baverage Yang Terdaftar Di Bursa Efek Indonesia 2010-2015) - Listanty, Nova, Drs. Ma'ruf, MM (2017)
The purpose of this study was to determine the effect of Economic Value Added (EVA), Return on Assets (ROA) and Return on Equity (ROE) on stock prices in the manufacturing sector of food and baverage listed in Indonesia Stock Exchange 2010-2015 period. The sampling technique used purposive sampling technique pemilihaan engineering samples based on certain characteristics. Data obtained by the publication of Indonesia Stock Ecxhange (IDX) in 2010-2015. The amount of data that meet the criteria of 11 companies to obtain the data 66 to 53 data and processed data. The analytical method of research is the classical assumption test, multiple linear analysis, R2, t test and F. The results of the data analysis and hypothesis testing we concluded that the variables simultaneously EVA, ROA and ROE have a significant effect on stock prices. Partially ROE significant effect to stock prices while variable ROA EVA and no significant effect on stock prices. In the variable EVA, ROA and ROE were able to explain the share price by 40.7% and the remaining 53.3% influenced by other factors.